Survey on Integrating of Renewable Energy into the Mining Industry - Zharan, Kateryna; Bongaerts, Jan C. (Journal of Environmental Accounting and Management, 2026)
Mining operations are energy intensive. The share of energy costs in total share is often reported to be in the range of 30-35%. Saving energy costs is therefore an economical key element of any mine operator. With the improving reliability and security of renewable energy sources, and the requirements to reduce carbon dioxide emissions, perspectives for using RE in mining operations emerge. In fact, these aspects are stimulating the mining companies to search for ways to substitute fossil energy with RE. Survey research is novel on this topic. Hereby, this paper estimates the data of a survey conducted among mining and renewable energy experts. Towards the data estimation, this study applies the following methods. Here, first, to develop the survey we summarized and reviewed the findings from the previous literature reviews using the Systematic Literature Review. Thus, the survey was developed to gather the expert’s knowledge and opinions on incentives for mining operators to turn to RE, barriers and challenges to be expected, environmental effects, appropriate business models and the overall impact of RE on mining operations. Secondly, to analyze outcomes of the survey the frequency evaluation has been developed and applied. Thirdly, using the Null Hypothesis and Alternative Hypothesis methods three hypotheses have been developed. Finally, the outcomes of the survey allow for identifying the factors that favor and disfavor decision-making on the use of RE in mining operations.